A Study on the Need of Financing of Capital Expenditures of Indian Corporate Sector: The Role of Indian Corporate Sector in Financing Capital Expenditures (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The pattern and pace of long-term investment is crucialin the development of every economy. The rate of capital accumulation orbusiness fixed investment is one of the key determinants of economy’s long termgrowth rate and is indispensable for overall economic development. The role ofIndian corporate sector has always been instrumental in this regard. Moreover,the same has become even more significant after the liberalization,privatization and globalization measures post Industrial Policy 1991 in Indianeconomy. Investment as such contributes towards current demand, currentemployment and future output. It therefore becomes interesting to studyinvestment at aggregate, industry and firm level. The investment pattern canalso indicate impact of monetary and fiscal policy on the corporate sector.“Investment spending is devoted to increasing or maintaining the stock ofcapital. The stock of capital consists of factories, machines, offices andother durable man-made products used in the process of production. The capitalstock also consists of residential housing as well as inventories” Over thelast decade and a half, Indian economy has witnessed a widespread change in itsorientation towards the role of state and private enterprises in contributingtowards economic growth. One of the primary objectives of liberalisationthrough Industrial Policy 1991 was to ensure that a market-oriented economywould infuse capital expenditures by corporate India to connect to the globaleconomy and push the country’s growth rate.